2022
DOI: 10.1093/plcell/koac363
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonate activates a CsMPK6-CsMYC2 module that regulates the expression of β-citraurin biosynthetic genes and fruit coloration in orange (Citrus sinensis)

Abstract: Carotenoids are natural pigments that influence the color of citrus fruit. The red-colored carotenoid β-citraurin is responsible for the peel color in ‘Newhall’ orange (Citrus sinensis). Although jasmonates are known to regulate the biosynthesis and accumulation of carotenoids, their effects on β-citraurin biosynthesis in citrus fruit remain unclear. Here, we determined that treatment with methyl jasmonate (MeJA) significantly promotes fruit coloration and β-citraurin production in ‘Newhall’ orange. A MeJA tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…The concentrations of JA, MeJA, JA-Ile and OPDA in our study increased significantly under the addition of MeJA ( Figure 3 ). Similar results were confirmed by the reports of Yue et al. (2023) and Mandal et al.…”
Section: Discussionsupporting
confidence: 92%
“…The concentrations of JA, MeJA, JA-Ile and OPDA in our study increased significantly under the addition of MeJA ( Figure 3 ). Similar results were confirmed by the reports of Yue et al. (2023) and Mandal et al.…”
Section: Discussionsupporting
confidence: 92%
“…32 The master regulator of jasmonate responses, CsMYC2 (belonging to bHLH family) could activate the expression of the CsCCD4b gene responsible for β-citraurin biosynthesis and CsPSY, CsLCYb, and CsBCH genes responsible for fruit peel coloration and promoted expression of the mitogen-activated protein kinase gene CsMPK6. 33 In turn, CsMPK6 interacted with CsMYC2 to decrease the promoter-binding activity of CsMYC2 to its target promoters, 33 suggesting that negative feedback regulation attenuates jasmonate signaling during the jasmonate-induced coloration of citrus fruit.…”
Section: Regulation Of Carotenoid Biosynthesis By Regulators In Plant...mentioning
confidence: 99%
“…Rehman et al [60] reported that the preharvest spray application of MeJA induced carotenoid accumulation and accelerated fruit coloration in flavedo of M7 Navel orange. In the study of Yue et al [61], it was found that the postharvest exogenous MeJA treatment promoted the β-citraurin production and fruit coloration in Newhall orange by inducing the expression of the transcription factor MYC2, which substantially activated the expression of the key β-citraurin biosynthetic genes (CCD4b, PSY, LCYB, and HYb). Different from the flavedo, MeJA negatively regulated carotenoid accumulation of the juice sacs of citrus fruit.…”
Section: Jasmonatementioning
confidence: 99%